VALIDITAS MODUL PEMBELAJARAN ELEKTRONIK BERORIENTASI PENDEKATAN KONTEKSTUAL PADA MATERI INOVASI TEKNOLOGI BIOLOGI - Chi Ami Novrita, Indhi; Yogica, Relsas (Universitas Cokroaminoto Palopo, 2025)
The aim of this research is to develop an electronic learning module oriented towards a contextual approach to valid biological technology innovation material. This research is development research using the ADDIE development model developed by Branch (2009). This research was carried out to the development stage, namely to the expert validation step, involving 2 lecturers as validators. The instrument used is a product validity test instrument. The data analysis technique used is qualitative and quantitative descriptive analysis. Based on the research conducted, a product has been produced in the form of an electronic learning module oriented towards a contextual approach to Biological Technology Innovation material. The validity test results with an average value of 88.54% meet the valid criteria. The research concluded that the electronic learning module oriented towards a contextual approach to Biological Technology Innovation material was valid.